41: Variation in Incidence of Cerebral Palsy (CP) in Preterm Infants in the Canadian Neonatal Follow-Up Network (CNFUN): 2009–2011. Issue 6 (1st June 2014) - Lodha, A; Sauve, R; Ballantyne, M; Creighton, D; Majnemer, A; Moddemann, D
Abstract: BACKGROUND: The Canadian Neonatal Follow-Up Network (CNFUN) has followed the developmental outcomes of all survivors of preterm birth <29 weeks gestation in 26 centres across Canada. The variation in the incidence of CP in Canadian NICUs is not known. OBJECTIVES: To determine the incidence, severity and type of cerebral palsy in preterm infants admitted to CNFUN NICUs in Canada. DESIGN/METHODS: Preterm infants born <29 weeks of gestational age (GA) in CNFUN between April 1, 2009 and July 1, 2011 were evaluated between 18 and 24 months corrected age (CA) using standardized criteria. Demographic and neurodevelopmental outcomes, specifically incidence, severity and type of CP were compared according to GA and birth weight (BW) categories by using Pearson χ 2 or Fisher exact test for categorical variables and ANOVA F-test for continuous variables. RESULTS: Of 2528 infants, 419 were not followed up and CP status was missing in 45. The number of infants evaluated as confirmed CP, suspect CP and no CP were 140 (6.8%), 72 (3.5%) and 1852 (89.7%) respectively. In CP, suspect CP and no CP groups, the mean BW was 908 g (223), 929 g (205) and 943 g (224) (P=0.18) and median GA was 26 weeks (25 to 27 weeks), 27 weeks (25 to 27 weeks) and 27 weeks (25 to 28 weeks) (P<0.01) respectively. The incidence, severity and type of CP by GA and BW are shown in Table 1 and Figure 1 respectively. Variation in incidence of cerebral palsy was observed in preterm infants born in Canada's NICUs. CONCLUSIONS: This study provides population-based information about incidence of cerebral palsy in preterm infants admitted to Level 3 NICUs in Canada over a two-year period. The incidence of CP is greatest in the extremely preterm infants born <26 weeks of GA. The incidence of CP varies among CNFUN centers and in various centres in Canada will be explored further.